Association between visceral obesity and 10-year risk of first atherosclerotic cardiovascular diseases events among American adults: National Health and Nutrition Examination Survey - Liying Zheng; Liying Zheng; Aochuan Sun; Aochuan Sun; Senfu Han; Senfu Han; Rongming Qi; Rongming Qi; Rumeng Wang; Rumeng Wang; Xiao Gong; Xiao Gong; et al. (Frontiers in Cardiovascular Medicine, 2023)
BackgroundIn the United States, the relationship between visceral obesity and the risk of developing atherosclerosis cardiovascular disease (ASCVD) for the first time in 10 years is unclear.MethodsData for this cross-sectional study came from the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2020. We collected variable information related to 10-year ASCVD risk and visceral obesity reliable indicators [Visceral obesity index (VAI) and Lipid accumulation product (LAP)]. And we used multiple logistic regression to analyze the correlation of visceral obesity indicators (VAI and LAP) with 10-year ASCVD risk. In addition, we assessed the linear relationship between VAI or LAP and 10-year ASCVD risk by smoothing curve fitting. Finally, we conducted subgroup analysis and sensitivity analysis after excluding participants with extreme VAI and LAP values to ensure that we obtained accurate and reliable results.ResultsOur study included a total of 1,547 participants (mean age: 56.5 ± 10.1, 60% of males). The results of the multiple logistic regression showed that compared with participants with the lowest VAI in the 1st Quartile (≤0.79), the adjusted OR values for VAI and elevated 10-year ASCVD risk in Q3 (1.30–2.14), and Q4 (≥2.15) were 2.58 (95% CI: 1.24–5.36, P = 0.011), 15.14 (95% CI: 6.93–33.05, P < 0.001), respectively. Compared with participants with the lowest LAP in the 1st Quartile (≤28.29), the adjusted OR values for VAI and elevated 10-year ASCVD risk in Q3 (46.52–77.00), and Q4 (≥77.01) were 4.63 (95% CI: 2.18–9.82, P < 0.001), 16.94 (95% CI: 6.74–42.57, P < 0.001), respectively. Stratified analysis showed that the association between VAI or LAP and the first ASCVD event was more pronounced in males.ConclusionHigher VAI or LAP scores are significantly associated with elevated 10-year ASCVD risk in adults aged 40 to 79 in the USA, which suggested that monitoring visceral obesity is crucial to reduce the risk of a first ASCVD event.